2023
DOI: 10.1108/agjsr-08-2022-0144
|View full text |Cite
|
Sign up to set email alerts
|

Phytotherapies for COVID-19 in Latin America and the Caribbean (LAC): Implications for present and future pandemics

Abstract: PurposeThis review aims to provide synoptic documentation on acclaimed anecdotal plant-based remedies used by Latin America and the Caribbean (LAC) communities to manage COVID-19. The theoretical approaches that form the basis for using the anecdotally claimed phytotherapies were reviewed against current scientific evidence.Design/methodology/approachIn this paper plant-based remedies for managing COVID-19 were searched on social and print media to identify testimonies of people from different communities in L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…To tackle the challenges of COVID-19 and prepare for future pandemics, Husaini et al (2023) remarked that an indigenous remedial approach to the management of COVID-19 was adopted as evident in many regions across the globe resorting to homemade/local preventive and curative medicinal approach. Another perspective on the local approach in the management of COVID-19 is in the area of technology adoption in workplaces, especially by the big tech-giant countries like China that quickly resorted to the policy of continuous education of her citizens while at home through the windows of ICT devices (Zhang et al, 2020).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…To tackle the challenges of COVID-19 and prepare for future pandemics, Husaini et al (2023) remarked that an indigenous remedial approach to the management of COVID-19 was adopted as evident in many regions across the globe resorting to homemade/local preventive and curative medicinal approach. Another perspective on the local approach in the management of COVID-19 is in the area of technology adoption in workplaces, especially by the big tech-giant countries like China that quickly resorted to the policy of continuous education of her citizens while at home through the windows of ICT devices (Zhang et al, 2020).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Due to Africa’s rich flora and fauna, the continent has extensively used medicinal plants for various ailments, even before scientific discoveries [ 204 ]. Medicinal plants still play a vital role in treating any disease in Africa, and in many communities, they are the primary healthcare or integrated into the healthcare system [ 222 , 223 ]. The World Health Organization reported that as of 2020, more than 34 research institutes on the African continent are dedicated to indigenous medicinal research, with approximately forty countries having traditional medicine policies [ 224 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the various modalities of T/CM that have been identi ed, the use of chamomile, honey, cinnamon, lemon, and eucalyptus were most prevalent. The increased use of chamomile and eucalyptus could potentially be attributed to the pandemic situation, given their historical roles in treating respiratory conditions across many Latin American countries 37,43 . However, caution must be exercised when consuming chamomile because while safe in moderate amounts, excessive consumption can act as a uterine stimulant and has been associated with premature constriction of fetal ductus arteriosus 38,44 .…”
Section: Discussionmentioning
confidence: 99%